2016
DOI: 10.1186/s13071-016-1757-1
|View full text |Cite
|
Sign up to set email alerts
|

Equine Cyathostominae can develop to infective third-stage larvae on straw bedding

Abstract: BackgroundDomesticated grazing animals including horses and donkeys are frequently housed using deep litter bedding systems, where it is commonly presumed that there is no risk of infection from the nematodes that are associated with grazing at pasture. We use two different approaches to test whether equids could become infected with cyathostomines from the ingestion of deep litter straw bedding.MethodsTwo herbage plot studies were performed in horticultural incubators set up to simulate three straw bedding sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Mas-Coma et al [22] reported that the first transmission of Fasciola spp. in Egypt was by a snail that was not related to the family Lymnaeidae (Biomphalaria alexandrina, and Planorbidae); this snail needs swampy areas such as low streaming lakes that allow sufficient moisture for the survival of infective metacercariae [23].…”
Section: Discussionmentioning
confidence: 99%
“…Mas-Coma et al [22] reported that the first transmission of Fasciola spp. in Egypt was by a snail that was not related to the family Lymnaeidae (Biomphalaria alexandrina, and Planorbidae); this snail needs swampy areas such as low streaming lakes that allow sufficient moisture for the survival of infective metacercariae [23].…”
Section: Discussionmentioning
confidence: 99%
“…As the questionnaire only involved data concerning management practice in 2013, it is possible that the presence of F. hepatica infection in non-grazing farms was a result of persisting infection acquired prior to 2013. However, other routes of infection, such as metacercariae-contaminated freshly cut grass and hay, should not be disregarded [ 41 , 42 ]; some nematode parasites have also been shown to develop to infective stages on straw bedding [ 43 ]. Transmission by metacercariae-contaminated water is also possible, as it is a common route of transmission for human fasciolosis in the Americas [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…We underline the importance of housing and pasture hygiene in maintaining a lower burden of infection [ 48 , 49 , 50 ]. Moreover, recent studies have shown the possibility for equine cyathostomins to develop to infective larvae on straw bedding [ 51 ], so more studies are required to further investigate the burden of different management practices.…”
Section: Discussionmentioning
confidence: 99%